On Being Human : Where Medicine, Ethics and Spirituality Converge - Guy Bourgeault (Presses de l'Université de Montréal, 2002)
At first glance, Western humanism, Japanese Buddhism and modern science have so little in common that the very idea of seeking common ground through dialogue seems overly idealistic. Only a man the calibre of Daisaku Ikeda could bring such a project to fruition. Firmly setting aside cliché and facile answers, he broaches the grand questions that face today's society: cancer, AIDS, death with dignity, in vitro fertilization, biomedical ethics... The responses offered by René Simard, molecular biologist and geneticist, and Guy Bourgeault, bioethicist, are insightful and compelling. Their discussions cut through linguistic and cultural barriers to present a vision of the potential - an the inherent challenges - of being human.